Evidence for multiple populations in the intermediate-age cluster Lindsay 1 in the SMC - Hollyhead, Katie; Kacharov, Nikolay; Lardo, C.; Bastian, Nate; Hilker, Michael; Koch-Hansen, Andreas; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society. Letters, 2017)
Lindsay 1 is an intermediate-age (≈8 Gyr) massive cluster in the Small Magellanic Cloud. Using VLT FORS2 spectra of 16 probable cluster members on the lower red giant branch of the cluster, we measure CN and CH band strengths (at ≃ 3883 and 4300 Å, respectively), along with carbon and nitrogen abundances and find that a sub-population of stars has significant nitrogen enrichment. A lack of spread in carbon abundances excludes evolutionary mixing as the source of this enrichment, so we conclude that this is evidence of multiple populations. Therefore, Lindsay 1 is the youngest cluster to show such variations, implying that the process triggering the onset of multiple populations must operate until at least redshift ∼1.